Does foreign presence stimulate creative destruction in local markets? - Mika Maliranta; Satu Nurmi (The Research Institute of the Finnish Economy (ETLA), 2007)
This paper studies the effect of foreign-owned companies (FOCs) in the region on establishment survival and growth in the Finnish business sector. We analyze whether the presence of the FOCs has asymmetric effects among the local businesses. Foreign presence in the region is measured in a novel way by using the regional links between establishments and their workers in the local labour markets. Evidence for small service establishments suggests that the presence of the FOCs contributes to aggregate productivity by cleansing inefficient units. The FOCs do not seem to stimulate productivity-enhancing restructuring among large, manufacturing or continuing establishments.
Keywords: F23; J23; R11; R23; 330; Foreign ownership; local labour markets; survival; growth; company efficiency; selection; reallocation; Technischer Fortschritt; Unternehmensentwicklung; Arbeitsproduktivität; Multinationales Unternehmen; Regionaler Arbeitsmarkt; Schätzung; Finnland